Kehidupan Sosial-Ekonomi Masyarakat Transmigrasi Tahun 2019-2025 - Wijaya, Kadek; Sarkowi; Ratna Wulan Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to examine the historical and socio-economic dynamics of the Balinese transmigration community in Karya Makmur Village, Nibung District, North Musi Rawas Regency, from 2019 to 2025. This study uses a descriptive qualitative method with data collection techniques such as observation, in-depth interviews, and documentation. The results show that the Balinese community has succeeded in maintaining its cultural identity and social structure through the preservation of customs and Hindu religious activities such as Galungan and Nyepi. However, economically, they have experienced significant transformation. The decline in rubber prices and yields since 2020 has encouraged agricultural diversification towards commodities such as chilies, bananas, and oil palm. Oil palm then became the dominant commodity with production reaching 18,796 tons in 2025. The conclusion of this study confirms that the success of transmigration is determined not only by physical factors such as land and infrastructure, but also by cultural resilience and the community's ability to adapt to economic changes. Keywords: Agricultural Economy, Local History, Social Adaptation, Transmigration.